Accelerators, Gantries, Magnets and Imaging Systems for Particle Beam Therapy: Recent Status and Prospects for Improvement - Collings, Edward W.; Lu, Lanchun; Gupta, Nilendu; Sumption, Mike D. (Frontiers in Oncology, 2022)
The review begins by emphasizing the clinical and commercial importance of therapy with beams of charged particles such as protons and carbon ions. It also refers to the manufacturers of such systems of which, by April 2021, more than 120 have been installed or are under construction worldwide. A general review of charged particle therapy systems refers to six manufacturers and provides in tabular form some details of systems installed in the U.S., Europe, Asia, and elsewhere. In a description of the principles of particle beam therapy a comparison is made of the properties of photons (x-rays) versus protons and protons versus carbon ions. A brief discussion of accelerators in general is followed by descriptions of cyclotrons (including the isosynchronous cyclotron and the synchrocyclotron) and synchrotrons. An interesting case study describes the evolution of a normal-conducting 220 ton cyclotron into an iron-free synchrocyclotron weighing only 5 tons. After acceleration the general principles of beam handling are gantry design are described. Subsequent sections describe gantry magnets in detail - normal conducting gantry magnets, superconducting gantry magnets for proton- and carbon therapy, low temperature superconducting (LTS) and high temperature superconducting (HTS) magnet windings, and the choice of HTS-REBCO conductors for cryogen-free carbon-ion gantries. Finally, an important “Prospect for Improvement” would be the introduction into the system of MRI image guidance. A well known property of the particle beam as it passes through tissue is its energy dependent absorption that rises to a pronounced peak (the Bragg peak) at the end of its range. In order to take advantage of this effect the exact targeting of the tumor and positioning of the patient must figure into the treatment. This need for direct visualization can be satisfied by magnetic resonance image guidance (MRI). In contrast to image-guided photon therapy, charged particle therapy requires the interaction of the imaging magnetic field with the particle beam to be taken into consideration. Modelling studies have been undertaken on the general topic of beam-line/magnetic field interaction using, for example, the software GEANT4 a platform for simulating the passage of charged particles through matter using a Monte Carlo method.